Directional dispersal has not evolved during the cane toad invasion. (12th January 2015) - Brown, Gregory P.; Phillips, Benjamin L.; Shine, Richard
Summary: The ability to disperse along a consistent compass heading strongly affects the rate and efficiency of an animal's displacement, and thus is under selection at the expanding edge of a biological invasion. We used radiotelemetry to assess whether the dispersal direction of cane toads ( Rhinella marina ) changed as a function of time since invasion, by comparing (i) toads at a single site monitored annually for 10 years subsequent to toad arrival; (ii) toads collected from sites across the species' invaded range in Australia, and radiotracked at a common site; and (iii) the offspring of those transported toads that were reared in captivity under common‐garden conditions. The first of these data sets showed non‐random directionality, indicating strong spatial sorting operating on this trait: toads moved in a north‐westerly direction for the first 6 years post‐invasion, but in random directions thereafter. Despite the evidence for trait sorting, no consistent directionality was seen in toads relocated from populations with different invasion histories nor in their offspring. Why do we see no evolutionary shifts? Dispersal directionality of the offspring was not correlated with that of their parents, arguing against a genetic basis to this behavioural trait. Thus, while an expanding invasion front creates an evolutionary pressure for animals to move in a specific direction, evolution of this trait has not occurred in this system because directionality is not heritable. The observed north‐westerly movements of toads at the invasion front were due to simple density differentials: in the first few years, most toads arriving at our study site originated from earlier‐colonized (and hence denser) populations to the south‐east. Abstract : Lay Summary